Crisis as a point of growth: Russia's positive economic experience - Solov'eva I. A. (Socio–economic landscape of the region: growth investments, 2025)
The article analyzes Russia's experience in overcoming crisis phenomena of various orientations in a historical context. The peculiarities of crisis management in society from the point of view of mentality are revealed, a unique feature is pointed out – the positive economic impact of the difficulties faced by the country on its economic development
Keywords: Великая Отечественная война; кризис; реформы; пандемия; санкции; российский менталитет; испытания